Extra Editorial: On the Release of Patron Data in Issue 58 of Code4Lib Journal - Code4Lib Editorial Board (Code4Lib Journal)
We, the editors of the Code4Lib Journal, sincerely apologize for the recent incident in which Personally Identifiable Information (PII) was released through the publication of an article in issue 58.